Further mechanics - Jefferson, Brian; Beadsworth, Tony. (New York : Hong Kong : Singapore : Oxford university press, 2001)
An A-Level text following on from Introducing Mechanics by the same authors. The two books cover all the requirements for Mechanics as part of a double-certificate Mathematics for any examination board. A clear text is supported by worked examples, exercises, and examination questions.
Includes index.
Keywords: Mechanics -- Study and teaching (Secondary) -- Great Britain; Mechanics -- Problems, exercises, etc; Mechanics -- Examinations, questions, etc